Fishing for Phytophthora in watercourses of the highly urbanized Swiss Plateau - Corine N. Schoebel; Simone Prospero; Daniel Rigling; Beat Ruffner (Mycological Progress, 2024)
Phytophthora species are a cause for concern due to their invasive potential and the damage they can cause in agriculture, forestry, and natural ecosystems worldwide. Since water plays a crucial role in their dispersal, stream and river baiting is commonly used to survey risk areas for the presence of quarantine Phytophthora species. However, our understanding of the distribution and diversity of Phytophthora species in European watercourses remains incomplete. This study investigated the presence and diversity of Phytophthora species in Swiss watercourses, with a focus on the highly urbanized Swiss Plateau. Over the period 2012–2016, we sampled 32 watercourses, including major rivers and smaller streams. We isolated Phytophthora on selective media and sequenced the internal transcribed spacer region to identify the species. We recovered 241 Phytophthora isolates, representing 11 species from five major clades. Phytophthora clade 6 prevailed, with P. lacustris being the most common, found in 94.7% of the watercourses. The number of Phytophthora species per watercourse ranged from one to five, with no correlation to watercourse complexity. Our study reveals the presence of six previously unreported species in Switzerland, while known invasive species were not found. Watercourses appear less suited to detect invasive pathogenic Phytophthora species with a still limited distribution in the environment.

Distribution, causal agents, and infection dynamic of emerging ink disease of sweet chestnut in Southern Switzerland - Simone Prospero; Malve Heinz; Eva Augustiny; Ying‐Yu Chen; Juanita Engelbrecht; Marina Fonti; Aliona Hoste; Beat Ruffner; Romina Sigrist; Noelani van den Berg; Patrick Fonti (Environmental Microbiology, 2023)
Emerging diseases caused by both native and exotic pathogens represent a main threat to forest ecosystems worldwide. The two invasive soilborne pathogens Phytophthora cinnamomi and Phytophthora × cambivora are the causal agents of ink disease, which has been threatening Castanea sativa in Europe for several centuries and seems to be re‐emerging in recent years. Here, we investigated the distribution, causal agents, and infection dynamics of ink disease in southern Switzerland. A total of 25 outbreaks were identified, 19 with only P . cinnamomi , 5 with only P . × cambivora , and 1 with both species. Dendrochronological analyses showed that the disease emerged in the last 20–30 years. Infected trees either died rapidly within 5–15 years post‐infection or showed a prolonged state of general decline until death. Based on a generalized linear model, the local risk of occurrence of ink disease was increased by an S‐SE aspect of the chestnut stand, the presence of a pure chestnut stand, management activities, the proximity of roads and buildings, and increasing annual mean temperature and precipitation. The genetic structure of the local P . cinnamomi population suggests independent introductions and local spread of the pathogen.

Oral insecticidal activity of plant‐associated pseudomonads - Beat Ruffner; Maria Péchy‐Tarr; Florian Ryffel; Patrik Hoegger; Christian Obrist; Alfred Rindlisbacher; Christoph Keel; Monika Maurhofer (Environmental Microbiology, 2013)
Summary Biocontrol pseudomonads are most known to protect plants from fungal diseases and to increase plant yield, while intriguing aspects on insecticidal activity have been discovered only recently. Here, we demonstrate that Fit toxin producing pseudomonads, in contrast to a naturally Fit ‐deficient strain, exhibit potent oral activity against larvae of S podoptera littoralis , H eliothis virescens and P lutella xylostella , all major insect pests of agricultural crops. Spraying plant leaves with suspensions containing only 1000 P seudomonas cells per ml was sufficient to kill 70–80% of S podoptera and H eliothis larvae. Monitoring survival kinetics and bacterial titres in parallel, we demonstrate that P seudomonas fluorescens CHA0 and P seudomonas chlororaphis PCL1391 , two bacteria harbouring the Fit gene cluster colonize and kill insects via oral infection. Using Fit mutants of CHA0 and PCL1391 , we show that production of the Fit toxin contributes substantially to oral insecticidal activity. Furthermore, the global regulator GacA is required for full insecticidal activity. Our findings demonstrate the lethal oral activity of two root‐colonizing pseudomonads so far known as potent antagonists of fungal plant pathogens. This adds insecticidal activity to the existing biocontrol repertoire of these bacteria and opens new perspectives for applications in crop pest control and in research on their ecological behaviour.